Algebraic and spectral analysis of local magnetic field intensity - Landauskas, Mantas; Vainoras, Alfonsas; Ragulskis, Minvydas (Lietuvos matematikos rinkinys, 2015)
One of the kind in Europe magnetometer is situated in central Lithuania and registers local magnetic field intensity. The sensitivity of the device is of pT (pico teslas) order. Magnetic field intensity is a real world sequence and as a result does not have a rank. Nevertheless, H-rank based techniques enable to analyse the data as algebraic sequences. The work also pays a considerable amount of attention to the spectral distribution of the signal. A specialized software is being developed due to the amount of the data and computational time costs for problems investigated.